2020
DOI: 10.21203/rs.3.rs-21025/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Atropine to Control Myopia Progression: A Systematic Review and Meta-analysis

Abstract: Background: The effect and safety of atropine on delaying the progression of myopia has been extensively studied, but its optimal effect dose is still unclear. Therefore, the purpose of this meta-analysis is to systematically evaluate the safety and effectiveness of atropine in controlling the progression of myopia, and to explore the relationship between the dose of atropine and the effect of controlling the progression of myopia. Methods: This work was done through the data search from PubMed, MEDLINE, EMBAS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Several previous studies have demonstrated associations of higher concentrations of atropine with more adverse effects such as photophobia and near-vision problems. 5,11 Our NMA showed similar results: the lower the atropine concentration was, the higher the ranking probabilities for safety profiles in pupil size and accommodation were. Although we were not able to obtain a reliable network for analysis of near BCVA, we can speculate that lower atropine concentration is correlated with lower possibility of decreased near BCVA, since accommodation and pupil size are components of near visual acuity.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 66%
See 3 more Smart Citations
“…Several previous studies have demonstrated associations of higher concentrations of atropine with more adverse effects such as photophobia and near-vision problems. 5,11 Our NMA showed similar results: the lower the atropine concentration was, the higher the ranking probabilities for safety profiles in pupil size and accommodation were. Although we were not able to obtain a reliable network for analysis of near BCVA, we can speculate that lower atropine concentration is correlated with lower possibility of decreased near BCVA, since accommodation and pupil size are components of near visual acuity.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 66%
“…Myopia also impacts children's overall quality of life, specifically in terms of academic performance, physical activity, social interaction, and future job choices. 5 Therefore, a treatment to effectively retard or even stop myopia progression in children is coveted by researchers, clinicians and medical practitioners.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous systematic review and meta-analysis have identified the efficacy and safety of atropine with ambiguous findings [20][21][22][23]. It was shown that the optimal dose of atropine may be 0.5% and 1% by Song et al [21] and equally beneficial by Gong et al [20], 0.01% by Zhao et al [22], and 0.05% by Zhao et al [23], but lacking consensus on atropine dose. As new clinical trials continually emerge, it is essential to conduct a meta-analysis to identify the optimal dose of atropine.…”
Section: Introductionmentioning
confidence: 99%